2021
DOI: 10.1021/acsaelm.1c00503
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable Strain Sensors Based on Two- and Three-Dimensional Carbonized Cotton Fabrics for the Detection of Full Range of Human Motions

Abstract: Recently, flexible strain/pressure sensors have made rapid development under the stimulus of the demand for wearable electronics. Those based on carbonized fabrics have attracted great attention by virtue of their outstanding sensing performance, facile fabrication, and low cost. However, it is still challenging for a stretchable sensor to achieve both a wide sensing range and high sensitivity up to now. Therefore, stretchable strain sensors based on carbonized cotton fabrics (CFs) with two-and three-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…In recent years, innovative E-textiles have been researched as wearable sensors based on electromechanical sensing principles, such as piezoresistivity, capacitance, and piezoelectricity. , Among all, the piezoresistive sensors excel in terms of extraordinary performance, ease of fabrication, direct measurement, and low energy consumption . High sensitivity and a wide operation range are typically required for pressure and strain sensors. , So far, researchers have presented many types of flexible electronic sensors based on different materials such as metal nanoparticles, carbonized silk fiber, , conductive polymer, gold nanowires, and graphene in order to achieve the predicted piezoresistive performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, innovative E-textiles have been researched as wearable sensors based on electromechanical sensing principles, such as piezoresistivity, capacitance, and piezoelectricity. , Among all, the piezoresistive sensors excel in terms of extraordinary performance, ease of fabrication, direct measurement, and low energy consumption . High sensitivity and a wide operation range are typically required for pressure and strain sensors. , So far, researchers have presented many types of flexible electronic sensors based on different materials such as metal nanoparticles, carbonized silk fiber, , conductive polymer, gold nanowires, and graphene in order to achieve the predicted piezoresistive performance.…”
Section: Introductionmentioning
confidence: 99%
“…13 In recent years, innovative E-textiles have been researched as wearable sensors based on electromechanical sensing principles, such as piezoresistivity, 14 capacitance, 15 and piezoelectricity. 16,17 Among all, the piezoresistive sensors excel in terms of extraordinary performance, ease of fabrication, direct measurement, and low energy consumption. 13 High sensitivity and a wide operation range are typically required for pressure and strain sensors.…”
Section: Introductionmentioning
confidence: 99%
“…He et al. [ 24 ] encapsulated carbonized weft‐KCFs as sensing layers in Ecoflex. The variation of the carbonized conductive network was significant because of the contact resistance changes of the interlocking coils.…”
Section: Flexible Strain Sensors Based On Natural Cellulose Fibersmentioning
confidence: 99%
“…[21][22][23] The carbonization temperature and time are the decisive factors for balancing the electrical conductivity and strain sensing performance of carbonized natural fiber materials. [24][25][26] Many studies found that although carbonized fibers exhibit excellent conductivity, they have a small strain range and high brittleness. Thus, they need to be combined with elastic polymers to improve their flexibility and strain capacity.…”
mentioning
confidence: 99%
“…A comparison of 2D and 3D structured strain sensors was designed to pronounce the achievement of good sensitivity and sensing range. The comparative results suggesting that the significance of the 3D structured strain sensor attained a broad sensing range from 0 to 180% [186]. Another step forward made to balance the sensitivity and sensing range of conductive composite PEDOT-based strain sensors via deploying the unique microstructures and stronger adhesion between PEDOT:PSS and one-dimensional (1D) AgNWs.…”
Section: Pedot Sensorsmentioning
confidence: 99%